Aging as a consequence of the adaptation-maladaptation dilemma - Lissek, Thomas (Advanced biology, 2024)
In aging, the organism is unable to counteract certain harmful influences over its lifetime which leads to progressive dysfunction and eventually death, thus delineating aging as one failed process of adaptation to a set of aging stimuli. A central problem in understanding aging is hence to explain why the organism cannot adapt to these aging stimuli. The adaptation-maladaptation theory of aging proposes that in aging adaptation processes such as adaptive transcription, epigenetic remodeling, and metabolic plasticity drive dysfunction themselves over time (maladaptation) and thereby cause aging-related disorders such as cancer and metabolic dysregulation. The central dilemma of aging is thus that the set of adaptation mechanisms that the body uses to deal with internal and external stressors acts as a stressor itself and cannot be effectively counteracted. The only available option for the organism to decrease maladaptation may be a program to progressively reduce the output of adaptive cascades (e.g., via genomic methylation) which then leads to reduced physiological adaptation capacity and syndromes like frailty, immunosenescence, and cognitive decline. The adaptation-maladaptation dilemma of aging entails that certain biological mechanisms can simultaneously protect against aging as well as drive aging. The key to longevity may lie in uncoupling adaptation from maladaptation.